PENINGKATAN KEAHLIAN TUKANG DAN BURUH BANGUNAN DALAM MEMBANGUN RUMAH SEDERHANA AMAN GEMPA DI KOTA PALU - Amir, Fatmawati; Martini, Martini; Luthfiah, Luthfiah (MEKTEK, 2013)
Aceh earthquake in 26 of December 2004 was changing the disaster risk management in Indonesia, particularly if it happened cause of seismic activity dan its secondary hazards, for instance : tsunami, landslide, debris flood and liquifaction, and made The Ministry of Public Work to initiated for revition the Indonesian Earthquake Map 2002 by invite the experts in earthquake. The result was translated in the Indonesian Seismic Zone Map 2010 and change Palu city particularly andÂ Sulawesi region, generally in high seismicity area with maximum magnitude in 7,9 Richter Scale. This map should made us to have prepareness for the risk possibility in immediate time by mitigation planning, one of the mitigation planning is Workmen training to build resinstantsimple houses from earthquake forconsumers safety and comfortability.The training coducted in 4 (four) steps, firstly :introduction and workmen groups choosing; secondly :programme explanation and socialization; thirdly : training center programme and lastly : monitoring and evaluation due to the result of training by visit workmen project and they could understanding and implementing the training moduls as well as possible.Keywords: Earthquake, Indoneisan Seismic Zone Map 2010, Workmen Training, City of Palu